Konsep Membangun Generasi “Tafaqquh Fid Din” di Pesantren Persatuan Islam (Persis) Cikarang Utara Kabupaten Bekasi - Wahidin; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Islamic Unity or remembered PERSIS is an Islamic organization according to Deliar Noer above as an Islamic organization that has a modern movement in the educational and social fields. Although the Islamic Union was born on September 12, 1923, it was only around the 1930s that the Islamic Union had a formal educational institution called "Islamic Education" or Pendis. This first education project was spearheaded by Mohammad Natsir (Former Prime Minister of Indonesia). This institution consists of several schools including Kindergarten, HIS (both established in 1930), MULO (1931) and a teacher's school or Kweekschool (1932). In March 1936, the Islamic Union inaugurated another educational institution called Pesantren Persatuan Islam. As the name implies, the educational institution established at the initiative of Ahmad Hassan or better known as A. Hassan is intended to form missionary cadres who spread religion in the midst of society. Research Method used by the author in providing information in accordance with the focus of research through qualitative methods with document review. Document review is considered as document analysis, which consists of books, articles, internet and materials appropriate to the research. As for the ways in which the data is collected. First, through a literature review that is in accordance with the material to be researched. Second, after the data has been obtained by the researcher, then analyze the data through descriptive methods in accordance with the author's understanding in conducting this study. The curriculum structure used by the Islamic Union Islamic Boarding School in North Cikarang can be seen how the portion of religious knowledge is very diverse without eliminating subjects that are commonly studied in other schools. This is one way this pesantren wants to produce a generation that is tafaqquh fid din in providing subject matter that prioritizes the basics of Islamic science. The responsibility of pesantren is very heavy, covering many aspects, religious responsibility and being able to master Islamic science "Tafaqquh Fid din" as well as the development of Islamic civilization and adorn themselves with "akhlak al-karimah". Therefore, the Islamic Union Pesantren, one of the educational institutions has a great responsibility to implement all of it, namely producing a generation that they not only understand Islamic religious science but also have good morals in the midst of society.